Gain-scheduled H∞ controller synthesis for actively steered longer and heavier commercial vehicles. (June 2020) - Sadeghi Kati, Maliheh; Fredriksson, Jonas; Jacobson, Bengt; Laine, Leo
This paper proposes a gain-scheduled controller synthesis for improving the lateral performance and stability of articulated heavy vehicles by active steering of the selected towed vehicle units. The longitudinal velocity is on-line measurable, and it is thus treated as a scheduling parameter in the gain-scheduled controller synthesis. The lateral performance of four articulated heavy vehicles, including existing Nordic heavy vehicles and prospective longer articulated heavy vehicles, are investigated with and without active steering and compared with a commonly used conventional tractor–semitrailer. The control problem is formulated as anH ∞ static output feedback, which uses only information from articulation angles between the steered vehicle unit and the vehicle unit in front of it. The solution of the problem is obtained within the linear matrix inequality framework, while guaranteeingH ∞ performance objectives. Effectiveness of the designed controller is verified through numerical simulations performed on high-fidelity vehicle models. The results confirm a significant reduction in yaw rate rearward amplification, lateral acceleration rearward amplification, and high-speed transient off-tracking, thereby improving the lateral stability and performance of all studied heavy vehicles at high speeds.